Iraq's oil - Friedemann Müller (Stiftung Wissenschaft und Politik (SWP), 2002)
The prospect of a military offensive against Iraq puts more than the price of oil into motion. It also causes further-reaching speculations on the extent to which Iraqi oil reserves and production capacities might serve as a motivation for the United States to intervene in Iraq. When Iraq's Foreign Minister, Naji Sabri, accuses the U.S. that its real interests lie in seeking to "destroy Iraq in order to control the Middle East oil," he is making an accusation that resonates in many commentaries from both Western and non-Western sources. Washington, in turn, strictly denies that oil represents a motive for threatening military intervention in Iraq. It does not deny, however, that such an intervention would have repercussions on international oil markets. (SWP Comments / SWP)
Keywords: 320